Weighting Criteria Evaluation between ASEAN NCAP and Industry Perception Using Analytic Hierarchy Process - N.H. Mokhtar; L. Hamzah; M.Z.M. Nasir; A.S.P. Singh; N.F. Azmi; A. Rahim; A. Ismail (Journal of the Society of Automotive Engineers Malaysia, 2024)
This study evaluates the weighting criteria for vehicle safety assessments, comparing the perspectives of the automotive industry with those of ASEAN NCAP, using the Analytic Hierarchy Process (AHP). The research aims to identify discrepancies in the prioritization of safety features and explore how these differences may influence vehicle safety standards in Southeast Asia. The analysis revealed significant variations in the ranking of key safety criteria such as Adult Occupant Protection (AOP), Child Occupant Protection (COP), and Safety Assist (SA). While ASEAN NCAP places a higher priority on foundational safety elements like AOP, the industry tends to prioritize advanced technologies, particularly within the SA category. These findings suggest a need for closer alignment between industry practices and regulatory frameworks to enhance overall vehicle safety. The study's insights are crucial for informing policy decisions and improving the effectiveness of safety regulations, thereby contributing to reduced fatalities and injuries on the roads in Southeast Asia.